Annotated bird sighting list for spring 1981 compiled by Thomas Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
An annotated list of birds sighted by Thomas Kent and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed